STRATEGI PEMASARAN JAJANAN PASAR PRODUK UMKM TERHADAP MINAT BELI MASYARAKAT DI DESA KOTA PARI - Yana Diana; Vina Arnita; Sri Rahayu; Fathul Fahrozi Nasution (Jurnal Nasional Teknologi Komputer, 2024)
The purpose of this study was to determine the application Strategy of the Product Quality, Packaging and Prices Traditional Cake of SMEs Products to Purchasing Decisions in Kota Pari Village. The specific target in this research to the community is that the village community knows the marketing strategy by improving product quality, packaging, and the appropriate selling price so that product sales will also increase. This type of research is quantitative research where the research instruments are observation, interviews, and distributing questionnaires. The data source of this research is the results of a questionnaire distributed to respondents who buy market snack cakes as many as 91 people. From this study it is known that product quality has a positive and significant effect on purchasing decisions. Packaging has a positive and significant effect on purchasing decisions and price has a positive and significant effect on purchasing decisions. It is hoped that the community as a household industry player in Kota Pari Village, Pantai Cermin Subdistrict, Serdang Bedagai Regency, can know and understand how to improve product quality, packaging and prices so as to increase sales and income.